2009
DOI: 10.1002/esp.1805
|View full text |Cite
|
Sign up to set email alerts
|

How soil conservation affects the catchment sediment budget – a comprehensive study in the north Ethiopian highlands

Abstract: An overall approach to assess the effectiveness of soil conservation measures at catchment scale is the comparison of sediment budgets before and after implementation of a catchment management programme. In the May Zeg-zeg catchment (187 ha) in Tigray, north Ethiopia, integrated catchment management has been implemented since 2004: stone bunds were built in the whole catchment, vegetation was allowed to re-grow on steep slopes and other marginal land, stubble grazing abandoned, and check dams built in gullies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 46 publications
5
96
0
1
Order By: Relevance
“…The intervention of SWC measures by the mobilization of the community has a significant soil loss reduction to protect their land from the rainfall-driven soil erosion. The effectiveness of SWC on runoff and sediment yield reduction has been reported in other studies in northern Ethiopia (Gebremichael et al 2005;Haregewyn et al 2005;Descheemaeker et al 2006;Mitiku et al 2006;Nyssen et al 2007Nyssen et al , 2009Dagnew et al 2015Dagnew et al , 2017.…”
Section: Discussionmentioning
confidence: 57%
“…The intervention of SWC measures by the mobilization of the community has a significant soil loss reduction to protect their land from the rainfall-driven soil erosion. The effectiveness of SWC on runoff and sediment yield reduction has been reported in other studies in northern Ethiopia (Gebremichael et al 2005;Haregewyn et al 2005;Descheemaeker et al 2006;Mitiku et al 2006;Nyssen et al 2007Nyssen et al , 2009Dagnew et al 2015Dagnew et al , 2017.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the cropland is generally sown at the beginning of the rainy season. At this time the fields have undergone at least two tillage operations, are bare and offer little resistance to splash and runoff erosion (Nyssen et al 2009a). Due to the long dry season and the large numbers of grazing livestock, most hillslopes are almost bare at the start of the rainy season.…”
Section: Suspended Sediment Concentrationsmentioning
confidence: 99%
“…Soil and water conservation (SWC) measures were found to have a profound impact on the SSY of small catchments in the Ethiopian highlands (Haregeweyn et al 2008;Nyssen et al 2009a). However, in this study, no significant correlation was found between all SSY-season values and the estimated stone bund (SB) density of each subcatchment (τ = -0.05, p = 0.784).…”
Section: Suspended Sediment Yield and Soil And Water Conservation Mementioning
confidence: 99%
See 2 more Smart Citations